Weapons prohibitions through immanent critique: NGOs as emancipatory and (de)securitising actors in security governance. Issue 4 (6th June 2018) - Petrova, Margarita H.
Abstract: The article examines the roles of NGOs in banning cluster munitions that resulted in the 2008 Convention on Cluster Munitions and the campaign against landmines in the 1990s. It argues that NGOs have managed to move questions about the use of force from the closed decision-making sphere of military commanders and arms control diplomats into open public debate. Thus NGOs have simultaneously desecuritised the use of force by states, securitised certain weapons technologies, and made human beings the referent object of security. This has marked a shift from state security and strategic disarmament to human security and humanitarian disarmament, without fundamentally challenging the laws of war. However, in contrast to realist views that only militarily useless weapons ever get banned and radical critical perspectives that see new legal regimes as legitimating war and US hegemony, I argue that NGOs have engaged in immanent critique of military arguments and practices based on prevailing principles of international humanitarian law. The resulting weapon ban treaties have both restrained US policy and undermined its legitimacy. The article explores the discursive choices that underpinned the remaking of the security agenda by NGOs and their role as de/securitising actors and emancipatory agents of change.